Systematic reviews: Structure, form and content. Issue 9 (September 2021) - Phillips, Veronica; Barker, Eleanor
This article aims to provide an overview of the structure, form and content of systematic reviews. It focuses in particular on the literature searching component, and covers systematic database searching techniques, searching for grey literature and the importance of librarian involvement in the search. It also covers systematic review reporting standards such as PRISMA-P and PRISMA, critical appraisal and tools and resources to support the review and ensure it is conducted efficiently and effectively. Finally, it summarizes the requirements when screening search results for inclusion in the review, and the statistical synthesis of included studies' findings.